Types of Words Meanings that Define the Cardinal Points - R. Ye. Telpov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The semantic structure of words that define the cardinal points is considered. Words of this type are of interest, on the one hand, as words embodying the most archetypal ideas about space, on the other hand, as lexemes in the structure of compound names of territories that have not received an official administrative status, but have distinct historical, cultural or socio-political characteristics (Russian North, East of Ukraine, etc.). The author proposes the classification of the components of the semantic structure of such words, developed by him, concludes that this structure is heterogeneous, that it is consistently realized in two meanings that are reflected in their lexicographic description: vector and territorial. The author draws attention to the fact that the territorial significance, in turn, is also subdivided into two types - general territorial and private territorial. The author emphasizes that the meaning of the names of the cardinal points should be considered private-territorial if they serve as a nomination for completely certain territorial entities that have a socio-political or cultural-historical originality. The author comes to the conclusion that, functioning in particular-territorial meanings, the names of the cardinal points are close to proper names: macrotoponyms and khoronyms, but they retain a special position among khoronyms and toponyms.